Disaster assessment for the "Belt and Road" region based on SDG landmarks. Issue 1 (2nd January 2022) - Wang, Li; He, Yuanhuizi; Zhang, Yuelin; Wang, Lei; Jia, Huicong; Zhou, Quan; Yu, Bo; Zhang, Meimei; Lin, Zhengyang; Chen, Fang
ABSTRACT: In this study, based on the EM-DAT (The Emergency Events Database) database, disaster assessment for the "Belt and Road" region was carried out in relation to the S D G 13.1.1 indicator of the Sustainable Development Goals (SDGs) agenda launched in 2015. A new method for diagnosing trends in the S D G 13.1.1 indicators based on the Theil-Sen median method is proposed. In addition, using the data available in the EM-DAT, an overview of disaster records is used to quantify disasters for a total of 73 countries. The disaster trends for the period 2015‒2019 were found to demonstrate the following. (1) As a result of geological and climate conditions, Asia and Africa are high-risk disaster areas and disasters have caused considerable economic losses and affected the populations in developing and underdeveloped countries in these regions. (2) The clear positive value of Δ s 13.1.1 found for China reflects the country's encouraging achievements in disaster prevention and mitigation. (3) The value of S D G 13.1.1 was observed to be increasing in South Asia, northwest Africa and South Africa, with the increase in India and Mauritania being the most serious. The new method proposed in this paper allows the real trend in the S D G 13.1.1 indicator in various countries to be derived and provides critical intelligence support for international disaster risk reduction plans and sustainable development goals.